The role of traditional leaders in service delivery : a case study of the Bushbuckridge Local Municipality in the Mpumalanga Province - Mdluli, Lucas Patson (My University, 2008)
Refer to the document
Thesis (M. Dev.) -- University of Limpopo, 2008
Keywords: Traditional leaders; Service delivery; Local municipalities; Drinking water; Poor health services; Poor road coditions; Municipal services -- South Africa -- Mpumalanga; Municipal government -- South Africa -- Mpumalanga; South Africa -- Kings and rulers; Traditional leaders; Municipal officials and employees